Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.18293/seke2022-098
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Mapping Study of Information Retrieval Approaches Applied to Requirements Trace Recovery

Abstract: Context: Requirements trace recovery (RTR) is always time-consuming, tedious, and fallible. There has been a growing interest in applying information retrieval (IR) to automate the process of recover trace links between requirements artifacts and other software artifacts. Objective: In this review, our objective is to identify the state-of-the-art of how IR has been explored to automate RTR and provide an overview of the research at the intersection of these two fields. Method: A systematic mapping study has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Wang et al provide a review of the intersection of RT and IR. They have summarized 21 enhancement strategies that can improve the performance of four kinds of IR technologies [3]. Torkar et al have concluded available tools and galore techniques for RT [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al provide a review of the intersection of RT and IR. They have summarized 21 enhancement strategies that can improve the performance of four kinds of IR technologies [3]. Torkar et al have concluded available tools and galore techniques for RT [4].…”
Section: Related Workmentioning
confidence: 99%
“…According to the four RQs of this study, the based search terms are defined as "requirements traceability" and "machine learning". In order to refine these search terms, alternative and related terms in the RT field are used to iteratively retrieve 5 databases according to the PICO standard [3]. The finalized search terms are as follows:…”
Section: ) Search Scope and Termsmentioning
confidence: 99%